Rosa x odorata â€œviridifloraâ€ (green rose) in Bali Botanical Garden: biological phenology and its propagation - HARTUTININGSIH M. SIREGAR; I PUTU SUENDRA; MUSTAID SIREGAR (Biodiversitas Journal of Biological Diversity, 2005)
Rosa x odorata â€œviridifloraâ€ (green rose) was one of rose collection in Bali Botanical Garden. This shrub had shiny, dark green leaves and sprays of rossete-shaped, double flowers, 4-5 cm across, green ageing to purplish green, with narrow petals that resemble sepals. Phenology flower research was begin from the growth phase and the development until the flower was fall, every phase was identified with one or more changing. Vegetative reproduction should take over for propagation purpose. Vegetative propagation was done by cutting about 15 cm long and 0.8-1.0 cm diameter. The study was carried out in the greenhouse of Bali Botanic Garden by using CompletelyRandomized Design with 5 treatments: rootone F powder, atonik 1 mL/L, atonik 2 mL/L, IBA 1 mg/L, NAA 1 mg/L and control. Each treatment was done 3 replication had 5 pieces of cutting. The result of research indicated that cutting more responsive to rootone F with highest cutting persentage (66,67%), highest to buds (25 days after planting) and to fast flowering (147 days after planting). Green rose is one of more flowers is not interested by pollinator insect.@2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: green rose, Rosa x odorata â€œviridifloraâ€, phenology.